Obstacles and Challenges in Gaining Access to Family Planning Services in Covid Era: A Cross-Sectional Descriptive Study (Indian Journal of Public Health Research & Development, 2023)
Introduction: Although WHO recommended continuing sexual and reproductive health services duringCOVID-19 pandemic, the services were either stopped completely or limited. Hence our study aims to determinethe challenges in the accessibility to family planning services as well as the impact on contraception and safeabortion services during COVID-19 era.Methods: This is a cross-sectional descriptive study conducted in the department of Obstetrics & Gynaecology,SRM hospital, Chennai from September 2021 to November 2021. Random sampling method was used to enrollparticipants after considering the inclusion and exclusion criteria.Results: Almost half of the study population (49.24%) faced difficulty in following any form of contraceptivemeasure amid pandemic. Non-availability of contraceptive supply (14.72%) was the major hurdle during thepandemic. Among the respondents who had terminated the pregnancy, the majority had done by general medicalpractitioner (66.67%) while only thirty-three percent terminated under specialist care. While comparing thecomplications during pregnancy termination, general medical practitioner approach led to more complicationsthan specialist care.Conclusion: Non-availability of contraceptive supplies, FP services amid COVID-19 pandemic has exerteddetrimental impact on the women reproductive health. Continuing FP and safe abortion services are essentialduring pandemic to sustain the success of high-quality reproductive services.
Keywords: Abortion, Contraception, COVID-19 pandemic, Family planning, Unwanted pregnancy